2006
DOI: 10.1017/s002193200600160x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Relationships of Income, Chronic Energy Deficiency, Morbidity and Hospitalization Among Adult Male Slum Dwellers of Midnapore, West Bengal, India

Abstract: A cross-sectional study of 212 adult (>18 years) male slum dwellers (mean age=34.6+/-14.4 years) of Midnapore town, West Bengal, India, was undertaken to study the inter-relationships of chronic energy deficiency (CED), monthly family income (MFI), self-reported morbidity and hospitalization due to severe illness. The mean height, weight and body mass index (BMI) of the subjects were 160.0 cm, 50.8 kg and 19.9 kg/m2, respectively. The overall frequencies of CED (BMI<18.5 kg/m2), morbidity and hospitalization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Undernourished elderly are more vulnerable to suffer from respiratory disease, poor quality of life, and all-cause mortality. [ 12 13 14 ] Economic dependency, lack of family support, and physical changes make elderly people vulnerable to suffer from undernutrition. Further, problems related to chewing and deglutition are considered to be the normal phenomena of geriatric life.…”
Section: Discussionmentioning
confidence: 99%
“…Undernourished elderly are more vulnerable to suffer from respiratory disease, poor quality of life, and all-cause mortality. [ 12 13 14 ] Economic dependency, lack of family support, and physical changes make elderly people vulnerable to suffer from undernutrition. Further, problems related to chewing and deglutition are considered to be the normal phenomena of geriatric life.…”
Section: Discussionmentioning
confidence: 99%
“…From our previous study [23] it has been revealed that the Fat% and other body composition increase with increase of nutritious food intake, which is indirectly correlated with family income. From The study of the other scientist [24,25] The regular physical activities as well as low diet might be the reasons for having hypotensive blood pressure in the workers.…”
Section: Discussionmentioning
confidence: 99%